Tradisi Ngabungbang Di Pondok Pesantren Cikalama Kabupaten Sumedang - Fijri Nabilah; Tarpin Tarpin (Priangan: Journal of Islamic Sundanese Culture, 2022)
The Ngabungbang tradition is held every 14 Rabiul Awal. not only followed by the community around the Cikalama Islamic Boarding School, but also by the entire community in various areas in West Java. In this tradition, there is a practice that is carried out at 00.00 on the night of 14 Rabiul Awal. This practice cannot be recited anywhere. The purpose of this study is to describe the Tradition of 14 Rabiul Awal which is called the Ngabungbang and the series of activities carried out in carrying out the Tradition of 14 Rabiul Awal. joinbang. The method used is the historical method through four stages, namely heuristics, criticism, interpretation, and historiography. The results of this study indicate that the Ngabungbang Tradition which is carried out at the Cikalama Islamic Boarding School is in the form of reciting the practices in which these practices may not be written, recorded or read outside the practice activities known as karahayuan science or prayer to ask for safety. The Ngabungbang tradition is held on the night of 14 Rabiul Awal. There are several conditions and rules that must be followed by every pilgrim who follows this tradition. The reading of these practices can only be led by a woman. The practice is recited continuously for 40 rounds and is followed by the congregation. The practice may not be written or recorded and also the practice may only be said on the night of 14 Rabiul Awal only.